A novel design for voltage inverting metamutator and its applications. (July 2021) - Arundeepakvel, R; Jatin,; Khatter, Parth; Pandey, Neeta; Minaei, Shahram
Abstract: This paper presents a novel structure of a versatile 4 port network that is used as a voltage inverting metamutator (VIM). The desired port relationships of proposed structure are obtained through proper interconnection of differential amplifiers, current mirrors and an inverting stage. The port relations are verified through both small signal analysis and simulations using 180 ​nm generic process design kit (gpdk) in Cadence Virtuoso tool. The performance of the proposed VIM is also examined by performing corner analysis and Monte Carlo simulations. By using proper port terminations, the proposed VIM is configured as current mode universal Filter, transconductance amplifier, transimpedance amplifier and memristor. All these applications are also verified for functionality.